Предмет: Алгебра,
автор: Аноним
упростите выражение и решите 12 и 13
Приложения:
![](https://files.topotvet.com/i/f45/f45ab7d4abf9bd5c593e39c3a0ad35c0.jpg)
Ответы
Автор ответа:
0
12.
(2x+5)²-(2x-3)*(2x+1)=4
4x²+20x+25-4x²-2x+6x+3=4
24x=-24 |÷24
x=-1.
13.
(b+1+1/(b-1)):(b²/(b²-2b+1)=((b+1)*(b+1)+1)/(b-1)):(b²/(b-1)²)=
=((b²-1)+1/(b-1)):(b²/(b-1)²))=(b²/(b-1)):(b²/(b-1)²)=b²*(b-1)²/(b²*(b-1))=b-1.
(2x+5)²-(2x-3)*(2x+1)=4
4x²+20x+25-4x²-2x+6x+3=4
24x=-24 |÷24
x=-1.
13.
(b+1+1/(b-1)):(b²/(b²-2b+1)=((b+1)*(b+1)+1)/(b-1)):(b²/(b-1)²)=
=((b²-1)+1/(b-1)):(b²/(b-1)²))=(b²/(b-1)):(b²/(b-1)²)=b²*(b-1)²/(b²*(b-1))=b-1.
Похожие вопросы
Предмет: Українська мова,
автор: oooooorej
Предмет: Қазақ тiлi,
автор: sonaivanidi
Предмет: Математика,
автор: gws3vpetia
Предмет: Алгебра,
автор: Аноним
Предмет: Химия,
автор: mariadovzik